The relationship between work–family conflict and job burnout among primary and secondary school teachers: the role of depression and cognitive reappraisal - Li, Yue; Ni, Xingcan; Zhang, Wei; Wang, Jianping; Yu, Chengfu; Zou, Hongyu (Frontiers in Psychology, 2024)
Background Primary and secondary school teachers are a high-risk group for job burnout, and how to alleviate their job burnout has become an increasingly urgent issue. Previous studies have paid less attention to the differential effects of the bidirectional interaction between work and family on the job burnout of the teachers. This study aim to explore the different impact of work–family conflict and family–work conflict on job burnout among primary and secondary school teachers, as well as its underlying mechanisms. Methods This study selected 2,184 primary and secondary school teachers in China (Mage = 37.26; SD = 9.40) as participants using a random sampling method. Using the SPSS Process 4.0 macro plugin constructed a moderated mediation model, the study explored the relationships between two different forms of work–family conflict, depression, cognitive reappraisal, and job burnout. Results The study results indicated that both forms of work–family conflict were significantly positively related to the job burnout, and this relationship was influenced by the mediating role of depression. Furthermore, cognitive reappraisal moderated the relationship between depression and job burnout. Conclusion This study revealed the potential pathways influencing job burnout among primary and secondary school teachers in the Chinese cultural context. Focusing on and alleviating work–family conflicts for primary and secondary school teachers is crucial for mitigating their occupational burnout. Additionally, teachers should also carefully and reasonably use cognitive reappraisal as an emotional regulation strategy to adjust the impact of depression on occupational burnout.